Medical image computing and computer assisted intervention – MICCAI 2018. 21st International Conference, Granada, Spain, September 16-20, 2018, Proceedings /: 21st International Conference, Granada, Spain, September 16-20, 2018, Proceedings. Part III : (2018) - Unknown
No abstract available